Angela Kronenburg Garcia's Zoom meeting transcript and report on Kenya, September 15, 2020 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2020)
To have access to the research data file, please contact: Angela Kronenburg: angela.kronenburg@uclouvain.be
Keywords: Arid regions; Maasai (African people); Food security; Livestock; East Africa; Kenya; COVID-19 Pandemic